Visceral adiposity index in patients with coronary artery disease, obesity and type 2 diabetes - A. A. Khorlampenko; V. N. Karetnikova; A. M. Kochergina; Yu. S. Ignatova; E. V. Belik; O. V. Gruzdeva; N. K. Brel; A. N. Kokov; O. L. Barbarash (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess visceral adiposity index (VAI) in patients with coronary artery disease (CAD) and overweight or obesity, as well as to determine its relationship with lipid and carbohydrate metabolism parameters and inflammatory markers, depending on the presence of carbohydrate metabolism disorders (CMD).Material and methods. The study included 95 patients with CAD and overweight (body mass index (BMI) >25 kg/m2) or obesity (BMI >30 kg/m2), of which 59 patients had type 2 diabetes (T2D) and 36 were without CMD. All patients were assessed for obesity; VAI was calculated. Following laboratory parameters were evaluated: glucose, glycated hemoglobin, C-reactive protein, adiponectin, lipid panel. In patients without history of CMD, an oral glucose tolerance test was performed.Results. Compared with patients without CMD, subjects with T2D had significantly higher values of BMI, waist circumference, as well as the body fat percentage, area and volume of visceral adipose tissue estimated by computed tomography. Analysis of lipid profile, C-reactive protein and adiponectin levels did not reveal significant differences between the groups. VAI also did not significantly differ in both groups. VAI had the most correlations with clinical and metabolic parameters in both patients with T2D and without CMD. Other methods for assessing obesity were less correlated with laboratory parameters in both groups. Only VAI significantly correlated with adiponectin in both groups.Conclusion. The obtained correlations between VAI and clinical and metabolic parameters confirm the practicability of using it to determine adipose tissue dysfunction in patients with/without CMD. The effect of increased VAI on the cardiovascular risk in high-risk patients requires further study.